Methods of Parental Treatment and Its Relationship with Emotional Stability among Female Students in Al-Mustansiriya University - Al-Jubouri, Zainab Hassan Falih; Hussein, Ali Radhi Abdul (Journal of Social Work and Science Education, 2022)
Parental treatment of children is one of the most important factors that play a key role in forming their personality. Equal and tolerant treatment makes the son realize the mercy of his parents towards him, and it has become clear to mental health scientists that the methods of parental treatment leave positive or negative effects on the children’s personality. If the son lives in a calm atmosphere dominated by love, tenderness, understanding and tranquility, he will be able to grow in a healthy way, but if the abuse situations increase and their intensity increases, then his personality will suffer from turmoil and conflict, and its effects will always accompany his personality and this will be reflected in the manifestations of his behavior and his emotional balance. The problem of the research lies in A study of negative parental treatment methods by fathers as perceived by the sons of female students of the Faculty of Physical Education and its relationship to emotional stability, the study aimed to identify the methods used in the treatment of children, as well as to know the relationship between the methods of parental treatment and the emotional stability of university students. As for the research hypotheses, there was a statistically significant correlation between the negative parental treatment style and the emotional stability of the research sample. The research sample consisted of (100) female students from Al-Mustansiriya University who were chosen randomly. The researchers used the descriptive approach in the survey style. The research tools were the emotional stability scale and the parental treatment methods scale. After conducting statistical treatments using the statistical program, the results of the research resulted in the existence of a significant correlation relationship. Statistically between the style of parental treatment and emotional stability among female students/Al-Mustansiriya University.